(untitled) (Bangladesh Journal of Otorhinolaryngology, 2023)
Background: Adenoid is a patch of tissue that is situated high up in the throat and just behind the nose in the nasopharynx. Adenoid along with the tonsils, is a part of the lymphatic system that clears away infection and keeps body fluids in balance.Whenever, adenoid become enlarged, seriously infected or causes certain complications, adenoidectomy becomes essential. It can be performed with many ways includingcoblation assisted adenoidectomy and conventional curettage adenoidectomy. Aim of the study: The aim ofthis study was to assessthe advantages of coblation assisted adenoidectomy over conventional curettage adenoidectomy. Methods: This comparative observational study was conducted in the Department of ENT, Bangladesh Medical College Hospital and Popular Medical College Hospital, Bangladesh during the period from July 2019 to June 2022. A total of 100 admitted patients for adenoidectomy were included as the study. All the participants were divided in two groups. In Conventional group, there were 50 participants selected for conventional curettage adenoidectomy.On the other hand, in coblation group, other 50 participants selected for coblation assisted adenoidectomy. For comparison of both the method all necessary data along with demographic and clinical status were collected in a predesigned questioner. All data were processed and analyzed and disseminated by using MS Office and SPSS version 23 programs as per need. Results: In this study, as the superiority of coblation assisted adenoidectomy over conventional curettage adenoidectomy we found significantly lower ‘intra operative blood loss in ml (7.58±3.28 ml)’, ‘post-operative bleeding (0%)’, presence of residual lymphoid tissue (8%)’, ‘days with analgesics (10.42±3.60 days), ‘post operative adenoid grading (0.0±0.0)’, ‘rate of recurrence (20%)’ and ‘needed days for recovery (4.68±2.17 days)’ among coblation group patients than that among conventional group patients. Conclusion: Coblation assisted adenoidectomy ensures more easier and specific treatment for the patient. As per the findings of this study we can conclude that, considering the attractive features like lower intra operative and post-operative blood loss, presence of residual lymphoid tissue, days with analgesics, post operative adenoid grading, rate of recurrence and needed days for recovery coblation assisted adenoidectomy may be considered as the method of choice for such treatment. Bangladesh J Otorhinolaryngol 2022; 28(2): 128-134